Existence and Uniqueness of Solutions for Time-Fractional Oldroyd-B Fluid Equations with Generalized Fractional Derivatives (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we study the existence and uniqueness of solutions for time-fractional Oldroyd-B fluid equations with generalized fractionalderivatives. We distinguish two cases. Firstly for the linear case, we get regularity results under some hypotheses of the source function and the initialdata. Secondly for the nonlinear case, we use the Banach fixed point theoremto obtain the existence and uniqueness of solutions.